Current Topics in Malaria 2016
DOI: 10.5772/65463
|View full text |Cite
|
Sign up to set email alerts
|

Resting Behaviour of Deltamethrin-Resistant Malaria Vectors, Anopheles arabiensis and Anopheles coluzzii, from North Cameroon: Upshots from a Two-Level Ordinary Logit Model

Abstract: The current study was conducted in Garoua, Pitoa, and Mayo-Oulo health districts of north Cameroon, in order to investigate the resting behaviour of deltamethrin-resistant Anopheles (An.) gambiae s.l. populations and build a model of their response to the use of Permanet 2.0 long-lasting insecticidal nets (LLINs). Adult mosquitoes were collected in October and November 2011, using spray catches and window exit traps in 29 clusters with LLINs in use. Sampled An. gambiae s.l. were identified down to species and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Recent studies conducted in West and East Africa have shown that indoor application of insecticides may induce intraspecific behavioural shifts towards early biting, exophagic biting and exophilic resting behaviour in malaria-transmitting mosquitoes [130,131,133]. Similarly, current studies conducted in Central Africa showed a comparable shift towards exophilic resting behaviour [134]. Mathematical modelling and field evidences have proved that these shifts in blood-feeding behaviour could threaten and impactonthecurrentcontrolprogrammes [132,135].…”
Section: Behavioural Resistance To Insecticides Used In Public Healthmentioning
confidence: 81%
“…Recent studies conducted in West and East Africa have shown that indoor application of insecticides may induce intraspecific behavioural shifts towards early biting, exophagic biting and exophilic resting behaviour in malaria-transmitting mosquitoes [130,131,133]. Similarly, current studies conducted in Central Africa showed a comparable shift towards exophilic resting behaviour [134]. Mathematical modelling and field evidences have proved that these shifts in blood-feeding behaviour could threaten and impactonthecurrentcontrolprogrammes [132,135].…”
Section: Behavioural Resistance To Insecticides Used In Public Healthmentioning
confidence: 81%
“…The synchronous presence of the four species across the collection methods may be related to the heterogeneity of their populations in terms of frequencies of physiological resistance to deltamethrin. Etang et al [49] previously reported a significant dependence of indoor relative densities of An. arabiensis and An.…”
Section: Discussionmentioning
confidence: 99%